Technical and Economic Analysis of Yamaha E15CMHL Outboard Engine Use for 3 GT Fishing Boat Propulsion in Tlocor Village - Ananto, M. Athallah Nandana Satya; Gafur, Abdul (MEIN : Journal of Mechanical, Electrical & Industrial Technology, 2025)
The fishermen in Tlocor village use 3 GT boat to do their works. They complained that the fuel of Yamaha E25BMHL outboard engine was wasteful when it is used for fishing. Based on these problems, it is necessary to conduct research on a 3 GT ship with a 25 HP engine capacity that is technically less feasible to use, so an engine with a lower power capacity is needed. As a solution, technical and economic analysis is needed to determine the appropriate use of outboard engines. The technical analysis stage by calculating resistance using the Holtrop method, comparison with Maxsurf Resistance Software, ship speed testing, and fuel consumption testing. The technical research results of the 3 GT ship have a Holtrop method resistance value of 1.39 kN, Maxsurf Software resistance is 1.4 kN, the speed of the ship that can be reached when the load conditions are 100% worth 7.139 knots with fuel consumption of 8.323 liters/hr for Yamaha E15CMHL engines, 7.291 knots with fuel consumption of 11.023 liters/hr for Yamaha E25BMHL engines. In terms of economics, the Yamaha E15CMHL engine has a BEP value of 44 days and the Yamaha E25BMHL has a value of 128 days, so the Yamaha E15CMHL outboard engine is more technically and economically suitable for use on 3 GT vessels.